Improving the economic performance of Russia’s energy system based on the development of alternative energy sources - Chikunov, Sergey O.; Gutsunuk, Olga N.; Ivleva, Marina I.; Elyakova, Isabella D.; Nikolaeva, Irina V.; Maramygin, Maksim S. (International Journal of Energy Economics and Policy, 2018)
An upward trend in conventional energy consumption and the exhaustibility of its resources, volatility of the prices for hydrocarbons in the global energy market update the development of scientific approaches to justification of the commercial efficiency of alternative energy in the Russian Federation. Integrated economic performance and environmental safety coefficients for generating companies in Russia were calculated through taxonomic analysis. Trends in the expenditure level for energy production in the context of alternative and conventional energy resources were forecasted by means of neural modeling technologies. Using an integrated assessment method, global priorities for the use of energy resources in Russia that would enhance the national energy system operation efficiency were identified. A forecasting integrated model of the Russian energy system development was elaborated, taking into account the commercial efficiency of alternative energy. Measures to stimulate energy production based on the use of alternative energy sources were proposed. Practical implementation of the research findings would contribute to Russia’s energy system restructuring and meeting the energy needs of the national economy to the fullest extent possible. Keywords: Alternative Energy Sources, Alternative Energy, Energy System, Economic Performance of Energy Production, Energy Resources, Conventional Energy JEL Classifications: L98; L16; O25 DOI: https://doi.org/10.32479/ijeep.7025